Occurrence of Hymenolepis diminuta (Rudolphi, 1819) in a Wistar White Rat from Guwahati, Assam, India - Devi, Pallabi; Deka, Abhijit; Hazorika, Mousumi (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Hymenolepis diminuta (Rudolphi, 1819) is a rodent tapeworm, having worldwide distribution. Occasionally it can also infest human, monkeys and dogs. Human acquires the parasite by accidental ingestion of intermediate host, with contaminated flour, cereal product, or dried fruits. In this case report the occurance of Hymenolepis diminuta, the rat tapeworm, is reported in a laboratory rat from Guwahati, Assam, India. The rat was showing complication of diarrhea, anorexia and depression. There is a history of death of two laboratory rat from the same laboratory having similar sign and symptoms. Coprological examination reveals characteristic ova of Hymenolepis diminuta which is slightly ovoid and brown with relatively thick shell. There are concentric striations in the outer membrane while the inner membrane is thin, containing six central hooklets but no polar filaments. Occurrence of this parasite is a cause of concern due to its zoonotic importance. Report of presence of this zoonotic parasite warranted a detailed systemic study to understand the bionomics of the parasite in the perspective of Assam.